PEMANENAN KAYU EKO-EFISIEN DI HUTAN ALAM MENDUKUNG KETAHANAN PEMBANGUNAN NASIONAL BERKELANJUTAN - Endom, Wesman; Nitibaskara, Tb. Unu (Universitas Nusa Bangsa, 2014)
Current management of natural forests or crops are facing a lot of problems. Among the big issues are issues of law and policy sentralistis, which is less supportive, practice the utilization that are not concerned with sustainability and the environment, a proliferation of Wild wood processing industry, logging, looting the land, forest fires, floods and landslides, drought, destruction of the wealth and diversity (biodiversity), as well as many other social problems again. It all became a part of the integral to be a consideration in an attempt to rebuild the forest and forestry. In this reform era, Manager of natural resources forest (SDH) should change the paradigm, which is based with the appropriate forest, environmental understanding is a comprehensive, long-term and eco-efficient. In an effort to achieve the goal in question, it is very necessary that harvesting methods and strategies of eco-efficient and appropriate, so that the results can be obtained in addition to wood, can be built to the maximum return of damaged forests, also exploiting the existing potential can still be managed effectively and efficiently, among others achieved by implementing eco-efficient (productive and minimum impacts